Generation of iron-reduction deficient mutants in Shewanella oneidensis MR-1 - Tan, Hui Ying (2019)
Shewanella oneidensis MR-1 is a gram-negative γ-proteobacterium that can use oxidizing molecules such as insoluble iron as terminal electron acceptors to respire anaerobically. S. oneidensis MR-1 is one of the most widely studied iron (III) reducing bacteria including dissimilatory iron (III) reduction. Iron (III) is present in circumneutral environments as highly insoluble oxides or hydroxides, which cannot come into direct contact with the microbial inner membrane: the site of the electron transport chain in gram-negative bacteria S. oneidensis MR-1. Therefore, it is hypothesized that S. oneidensis MR-1 must utilize a novel strategy for the effective respiration of solid iron (III) compounds. In this research, antibiotic mutagenesis procedures and a rapid mutant screening technique was used to screen S. oneidensis MR-1 iron-reduction deficient mutants unable to reduce iron (III) as electron acceptor. The iron (III) reduction-deficient mutant screening technique was based on the observation that wild-type S. oneidensis produced a black color colony precipitate during growth on iron (III) while colony results from mutagenesis do not. S. oneidensis MR-1 iron-reduction deficient mutants, 6-11A and 14-2A were generated in this study. Isolated mutants in this study retained the ability to reduce iron (III) to iron (II) when grew on M1 medium supplemented with both Hydrous Ferric Oxide, insoluble iron (III) and iron (III) citrate, soluble iron (III) coupled with lactate as the electron donor but in a slower rate compared to wild type S. oneidensis MR-1. Results of this study indicate that an iron-reduction deficient mutant have more than one pathway that can be employed to reduce iron (III). This study will provide information to the molecular understanding of iron (III) reduction of S. oneidensis MR-1.